Pulmonary Hypertension in Pregnancy: A Cardiological Approach to Maternal Outcomes as well as Neonatal and Therapeutic Management - Zainur Hafiz Yusa; Iqbal Maulana (Cardiovascular and Cardiometabolic Journal (CCJ), 2024)
Highlights: 1. Pulmonary hypertension is threatening to both the mother and the infant in the womb. 2. This report discusses the complexity of physiological changes in pregnant women with pulmonary hypertension. - Abstract Background: Maternal morbidity and mortality with pulmonary hypertension in pregnancy usually occur during labor until early postpartum. Historical reports have shown mortality rates as high as 30–56%. We report a 32-year-old female patient pregnant with her second child, with complaints of bleeding from the birth canal since 1 hour before admission to the hospital and a history of atrial septal defect type secundum. Case presentation: The patient was diagnosed with G2P1A0, 16–17 weeks pregnant, with death conception, thrombocytopenia, and ASD secundum with pulmonary hypertension. The patient was planned for dilation and curettage by the obstetrics and gynecology departments. As a result of consultation with the cardiology department, medication management was given, and the decision to tolerate CRI IV very high-risk surgery was given. Conclusion: Despite progress, pregnancy remains poorly tolerated in cases of pulmonary hypertension. Management should remain focused on contraceptive counseling and offering early termination when pregnancy does occur